Jews in Limbo: Decay of the State Authority in Galicia in 1918 as a Prelude to the Post-War Anti-Jewish Violence - Kutílek, Jan (My University, 2024)
"The economic situation in Galicia in the last year of the war was desolate. Protests, strikes, and looting marked the beginning of 1918. Then a wave of violence came in response to the Brest-Litovsk Treaty. Jews were considered a foreign element loyal to the hated central authorities and were often the targets of violence. After the national passions caused by the loss of the Chełm region due to the Brest-Litovsk peace cooled down, the violence caused primarily by food shortages emerged. Jews perceived as dishonest merchants were often the victims of an angry mob. In the last months before the collapse of the Austro-Hungarian Empire, war exhaustion was steadily becoming more noticeable. The hardships caused by the lack of food as well as national and social stirrings worsened the overall situation."
Židé v limbu: Rozpad státní správy v Haliči v roce 1918 jako předehra k poválečnému protižidovskému násilí
Keywords: Anti-Jewish Violence; Galicia; Austria-Hungary; Poland; Food Riot; National Upheaval; Protižidovské násilí; Halič; Rakousko-Uhersko; Polsko; hladové bouře; nacionální nepokoje